The potential of astro-tourism in Poland: Gwiezdne Dolistowie in the Bieszczady mountains - Dylak, Igor (Who needs tourism?, 2024)
The article focuses on the presentation of astronomical tourism and its potential in Poland, as well as the example of Gwiezdne Dolistowie in the Bieszczady Mountains. It also outlines the activities that can be undertaken to practice astro-tourism and presents some unknown concepts in the field. The results of surveys conducted among the guests of the facility and random individuals, gave the most reliable basis for assessing the potential. The article formulates the author’s definitions: astro-tourism farm, astro-tourism product, astro-tourism potential.